Uma realidade em preto e branco: as mulheres vítimas de violência doméstica - Silva, Carla da (2011)
A reality in black and white: women victims of domestic violence, aims to analyze and understand the impact of actions undertaken in the care services ONG SOS Ação Mulher e Família e Centro de Referência e Apoio à Mulher CEAMO, in life dynamics for women experiencing domestic violence. By chapters, it was drew up a brief historical about the history of women in patriarchal society, the concepts were delineated, as well the issue of domestic violence against women; it was described the dynamics of institutions and studied their interventions with women victims of violence. The methodology used was qualitative research through focus group and individual interviews, which were divided in stages: the first stage of the research consisted of a focus group with five women ex-users of SOS and four individual interviews with women ex-users of CEAMO; in the second step was conducted a focus group with four professionals from different fields of knowledge, techniques of NGO SOS and CEAMO; in the third step, data was analyzed. The results showed that interventions implemented by professionals of those care services, guided by welcoming, listen carefully, with respect to the emotional time of each woman and empowerment, reflected positively on the dynamics of women's lives, transforming their realities and contributing to break the cycle of violence. It was found that the professionals of the two studied institutions perform their job with promptitude, with their initiatives impacting directly on the deconstruction of macho culture, fulfilling, this way, the goal of care services in treat, mitigate and halt the violence against women. It also remains evident that the issue of time to reconcile the emotional of victims, the urgency of action and the emotional of techniques in relation to expected attitudes to be taken by users, has a bounce in the dynamics of these professionals, creating feelings of anxiety and concern